Escola Itinerante Herdeiros do Saber: uma análise sobre o processo de transformação da “escola do ensino” à “escola do trabalho” - Souza , Rose Riepe de (2020)
This research was developed in the Research Line: Society, Knowledge and Education, of the Graduate Program in Education - Master's Degree, from UNIOESTE, Francisco Beltrão campus. The object of study refers to an Itinerant School of the Movement of Landless Rural Workers (MST) of Paraná and its process of transformation from the “School of Education” to the “School of Work”, which involve processes of pedagogical changes, school organization and pedagogical practices of teachers who work in Itinerant Schools. The school education proposal of this social movement, having work as an educational principle as one of its fundamental orientations, becomes important to be understood and analyzed, because they are related to the debates about the school form in processes of pedagogical transformations in rural schools. In this sense, the main question of the research concerns what the teachers conceive about the transformation process in relation to the “School of Education” to the “School of Work” that is under construction at the Herdeiros do Saber Itinerant School, Herdeiros da Terra pre-settlement of 1º de Maio, municipality of Rio Bonito do Iguaçu. The general objective of the research was to analyze the process of transforming the pedagogical practices of the “School of Education” to the “School of Work”, from the perspectives of the teachers working at the Herdeiros do Saber Itinerant School. The specific objectives are to: i) Identify and understand the configuration of the pedagogical form of the "School of Education"; ii) Identify and understand the configuration of the pedagogical form of the “School of Work”; iii) Identify and understand how the MST Itinerant School is conceived in the transformation of the “School of Teaching” to the “School of Work”; iv) Identify and analyze the configurations of the “Teaching School” present in the Itinerant School of the MST, from the perspective of the teachers working in the Herdeiros do Saber Itinerant School; v) To analyze the contradictions of the “School of Education”, present in the Herdeiros do Saber Itinerant School of the MST, which limit the progress in the transformation to the “School of Work”. As a methodological option, a qualitative research was carried out based on the case study, using semi-structured interviews, participant observation and field diary instruments. The theoretical framework used corresponds to authors who help to understand the school as an object of study, as well as its specificities in the pedagogical characteristics of the “School of Education”, “School of Work” and the Itinerant School of the MST. It covers authors such as: Pistrak (2011; 2013), Krupskaya (2017), Lunatcharski, (2012), Manacorda (2006), Petitat (1994), Enguita (1989), Vincent, Lahire and Thin (2001), Saviani (2006) , Canário (2006; 2005) and Munarim (2011), Bahniuk (2017), Caldart (2000; 2011, 2005), Dalmagro (2011), Munarim (2011), Souza (2006), Bahniuk, Camini (2012), Sapelli , Leite, Bahniuk (2019), Ciavatta and Lobo (2012), among others. The research consisted of enlarge the understanding of the pedagogical form of the “School of Education” and of the “School of Work” and of identifying the pedagogical form of the MST school and its specificities from the Itinerant Schools pedagogical proposal. The research pointed out some characteristics of the Herdeiros do Saber Itinerant School in the process of transformation of the predominant school form and the challenges experienced by this school, which can contribute to the advancement of this educational experience and other Itinerant Schools, from the Countryside and public schools. This work was carried out with the support of the Coordination for the Improvement of Higher Education Personnel - Brazil (CAPES) - Financing Code 001.